-6(x+2)=9x-3

Simple and best practice solution for -6(x+2)=9x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(x+2)=9x-3 equation:


Simplifying
-6(x + 2) = 9x + -3

Reorder the terms:
-6(2 + x) = 9x + -3
(2 * -6 + x * -6) = 9x + -3
(-12 + -6x) = 9x + -3

Reorder the terms:
-12 + -6x = -3 + 9x

Solving
-12 + -6x = -3 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
-12 + -6x + -9x = -3 + 9x + -9x

Combine like terms: -6x + -9x = -15x
-12 + -15x = -3 + 9x + -9x

Combine like terms: 9x + -9x = 0
-12 + -15x = -3 + 0
-12 + -15x = -3

Add '12' to each side of the equation.
-12 + 12 + -15x = -3 + 12

Combine like terms: -12 + 12 = 0
0 + -15x = -3 + 12
-15x = -3 + 12

Combine like terms: -3 + 12 = 9
-15x = 9

Divide each side by '-15'.
x = -0.6

Simplifying
x = -0.6

See similar equations:

| p^6-52p^4+640p^2-1024=0 | | 3(1-2x)+7= | | Y=-3x+180 | | 2p+3q+5r+7= | | -0.5x+0y=14 | | -7t+11=-73 | | (v^2-9v+18)(3v+27)=0 | | -18=8x-9x-5x | | w^2-w-18=0 | | 0=10t^2+25t-30 | | Ln(x+1)=0.43 | | 30x+20y=248 | | y+5x+13= | | ((ln)x)=10 | | ln(1-4k)=8k | | xy+x+y=23 | | tan(2x)=cos(x) | | -2[5-(5-4s)]+4=-3s | | 3x+4-2=9.5 | | 10-p=4p-12 | | 5(ln(x)/ln(7))-(ln(49x)/ln(7))=-2 | | -9(2+A)+4(2A+9)=1 | | 21x+3y-48=0 | | (7-2i)/(3-4i) | | 7y-8=y+4 | | 5x+3y=570 | | cos(X)=0.333 | | 6-5x=-46 | | x^2+y^2=8x+2y+12 | | 5m-3(m+1)=2m-10 | | 12(x+3)=-3(3+13) | | 6-(2-x)6-x=3(4x-1)-4 |

Equations solver categories